2006
DOI: 10.1099/vir.0.81184-0
|View full text |Cite
|
Sign up to set email alerts
|

Very virulent infectious bursal disease virus: reduced pathogenicity in a rare natural segment-B-reassorted isolate

Abstract: The purpose of this study was to compare the molecular epidemiology of infectious bursal disease virus (IBDV) segments A and B of 50 natural or vaccine IBDV strains that were isolated or produced between 1972 and 2002 in 17 countries from four continents, with phenotypes ranging from attenuated to very virulent (vv). These strains were subjected to sequence and phylogenetic analysis based on partial sequences of genome segments A and B. Although there is co-evolution of the two genome segments (70 % of strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
57
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(81 citation statements)
references
References 50 publications
10
57
0
3
Order By: Relevance
“…IBDV strain 94432 was originally identified as having both genome segments phylogenetically related to vvIBDVs (41,43) and exhibiting atypical antigenicity (44), most probably based on one amino acid change in the variable antigenic domain of VP2 (43). In this paper we confirm unpublished previous observations that 94432 replicates extensively in the BF but induces only mild clinical signs and does not cause mortality, thus exhibiting a clear discrepancy between its vvIBDV-related genotype and its mildly pathogenic phenotype.…”
Section: Nfectious Bursal Disease Virus (Ibdv) Of Chickens (Gallus supporting
confidence: 80%
See 2 more Smart Citations
“…IBDV strain 94432 was originally identified as having both genome segments phylogenetically related to vvIBDVs (41,43) and exhibiting atypical antigenicity (44), most probably based on one amino acid change in the variable antigenic domain of VP2 (43). In this paper we confirm unpublished previous observations that 94432 replicates extensively in the BF but induces only mild clinical signs and does not cause mortality, thus exhibiting a clear discrepancy between its vvIBDV-related genotype and its mildly pathogenic phenotype.…”
Section: Nfectious Bursal Disease Virus (Ibdv) Of Chickens (Gallus supporting
confidence: 80%
“…This observation is consistent with the phylogeny-based hypothesis that both genome segments may be involved in the emergence of vvIBDV (38,39). Recently, this hypothesis was substantiated by the isolation of three naturally occurring segment B-reassorted vvIBDV isolates, all with reduced pathogenicity in chickens (40,41). Another recent experimental study based on reverse genetics demonstrated that several domains of the IBDV polymerase may contribute to virulence (42).…”
Section: Nfectious Bursal Disease Virus (Ibdv) Of Chickens (Gallus supporting
confidence: 75%
See 1 more Smart Citation
“…Leucine (L) to Serine (S) amino acid change is noted in the same sample [31]. Remaining amino acid alterations were mostly conservative in nature [54][55][56][57]. The changes in the hydrophilic regions of the VP2 protein were important as they are indicative of continuous changes going on in viral genome [58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Nos últimos anos, o uso de técnicas moleculares como a RT-PCR (reação em cadeia da polimerase) tem sido útil na detecção e genotipagem das diferentes cepas de IBDV presentes no campo (NOUEN et al, 2006 ). A população constituída de aves que são criadas para o consumo próprio, conhecidas como galinhas de fundo de quintal, não é beneficiada com o programa de biosseguridade, aplicado nas criações comerciais.…”
Section: Introductionunclassified